Bionanocomposites of PLA/PBAT/organophilic clay: preparation and characterization - Barbosa,Josiane Dantas Viana (2019)
Abstract The objective of this study was to develop bionanocomposites from blends of poly(lactic acid) (PLA) and poly(butylene adipate-co-terephthalate) (PBAT) and from 3% and 6% bentonite clay. Initially, the bentonite clay was treated with Praepagen salt, and the properties of the modified clay were evaluated. After the organophilization of the clay was completed, 50:50 blends of PLA/PBAT were prepared, and 3 and 6% clay was added. To test the dispersion of the system, the blending sequence was performed using eight different sequences for the addition of clay to the PLA/PBAT matrices. The mixtures were prepared in a twin screw extruder, and the specimens were subsequently injection molded. The investigated mechanical and morphological properties included the yield strength, yield strain, tensile and bending elastic modulus, and scanning and transmission electron microscopy analyses. The results of this study showed increases of the mechanical properties when nanoparticles were added and the formation of bionanocomposites with intercalated structures.